Physical Activity on Oxygen Saturation and Pulse Frequency in Journalists Games 4th Participants in 2022 - Rora Asyulia; Sutanto Priyo Hastono; Margono Margono; Abd Halim; Yafi Velyan Mahyudi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
One of the Clean and Healthy Behaviors (PHBS) is doing activities every day. Physical activity can affect changes in one's oxygen saturation and pulse frequency. This study aims to see the effect of physical activity on oxygen saturation and pulse frequency in the 4th game journalist participants. This research was a pre-experimental type with a one group pretest-posttest research design. The selection of the research sample used a purposive sampling technique of 92 people with inclusion criteria ≥ 17 years. Oxygen saturation and pulse frequency data were collected using pulses oximetry, where measurements are taken after carrying out physical activities such as 3 on 3 basketball, badminton or futsal matches. The mean value of oxygen saturation before physical activity was 98.10, and decreased after physical activity, namely 97.79. The pulse frequency value before physical activity was 98.84 and it increased after physical activity, namely 108.37. The results of the calculation of the Wilcoxon Signed Rank Test for oxygen saturation obtained a value of p = 0.023 which means <0.05, while for pulse frequency the value obtained was p = 0.000 <0.05. The conclusion of this study is that there is a significant difference between physical activity on oxygen saturation values ​​and pulse frequency in the 4th game journalist participants.